2010
DOI: 10.1021/ja102004b
|View full text |Cite
|
Sign up to set email alerts
|

Enol Tautomers of Watson−Crick Base Pair Models Are Metastable Because of Nuclear Quantum Effects

Abstract: Intermolecular enol tautomers of Watson-Crick base pairs could emerge spontaneously via interbase double proton transfer. It has been hypothesized that their formation could be facilitated by thermal fluctuations and proton tunneling, and possibly be relevant to DNA damage. Theoretical and computational studies, assuming classical nuclei, have confirmed the dynamic stability of these rare tautomers. However, by accounting for nuclear quantum effects explicitly through Car-Parrinello path integral molecular dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
86
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(100 citation statements)
references
References 79 publications
14
86
0
Order By: Relevance
“…Several tautomerization mechanisms have been proposed. For example, intermolecular double-proton tunneling has been suggested for the spontaneous formation of enol tautomers in Watson-Crick base pairs (38) and has been observed for imidazole and pyrazole in nonaqueous solvents at −100°C (39). We precluded the possibility of dimer formation in water because both the FTIR spectra (23) and T-jump relaxation rates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several tautomerization mechanisms have been proposed. For example, intermolecular double-proton tunneling has been suggested for the spontaneous formation of enol tautomers in Watson-Crick base pairs (38) and has been observed for imidazole and pyrazole in nonaqueous solvents at −100°C (39). We precluded the possibility of dimer formation in water because both the FTIR spectra (23) and T-jump relaxation rates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…10,12,[41][42][43] The intramolecular PT mechanism has received a particular attention since nuclear quantum effects could inhibit the formation of certain tautomeric forms, which would avoid DNA 13 damage. 44 Yet, experimental evidences have indicated that tautomerism can provide a molecular explanation for the mutagenic properties. 34 Moreover, the intermolecular tautomeric equilibrium in electronic excited states 45 can favor specific tautomeric forms.…”
Section: Figurementioning
confidence: 99%
“…The combination of 4 bases and 20 amino acids are the correct solutions to a genetic information optimization problem with enzymes central to the quantum coherence (picture a particle in quantum mechanics where all of the alternative possibilities open to the system co-exist as a superposition in a pure state). Quantum directed mutations can theoretically occur via proton tunneling where protons can plow through the normal thermodynamic energy barrier and cause nucleotide bases to vacillate between two tautomeric states thus causing non-canonical base pairing and consequently mutations (Perez et al, 2010). DNA, acting as a quantum computer, can simultaneously examine and select a beneficial state (mutation) while held in superposition and then decohere, collapsing back into the classical world (McFadden et al 1999).…”
Section: Quantum Mechanics and The Matter Of Lifementioning
confidence: 99%